2010
DOI: 10.1017/s0007114510000541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet, sex and age on fatty acid metabolism in broiler chickens: SFA and MUFA

Abstract: The present study was conducted to evaluate the effect of different dietary lipid sources, age and sex on the SFA and MUFA metabolism in broiler chickens using a whole body fatty acid balance method. Four dietary lipid sources (palm fat, Palm; soyabean oil, Soya; linseed oil, Lin; and fish oil, Fish) were added at 3 % to a basal diet containing 5 % Palm. Diets were fed to female and male chickens from day 1 to either day 21 or day 42 of age. The accumulation (percentage of net intake and ex novo production) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
14
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 29 publications
7
14
1
1
Order By: Relevance
“…In fact, Kazala et al (1999) observed a negative relationship between the intramuscular fat content and the elongase activity in beef. Our results are in line with Poureslami et al (2010), who reported a significant increase in elongase with age in broilers. In a study on the fatty acid profile and lipid metabolism, Dal Bosco et al (2012) reported a significant effect of the genotype of the birds on the elongase activity.…”
Section: Resultssupporting
confidence: 93%
“…In fact, Kazala et al (1999) observed a negative relationship between the intramuscular fat content and the elongase activity in beef. Our results are in line with Poureslami et al (2010), who reported a significant increase in elongase with age in broilers. In a study on the fatty acid profile and lipid metabolism, Dal Bosco et al (2012) reported a significant effect of the genotype of the birds on the elongase activity.…”
Section: Resultssupporting
confidence: 93%
“…A decrease in digestibility was also observed for oleic acid (18:1) in CAM10 and FLAX10 diets. Overall, the current study showing reduction in the digestibility of unsaturated fatty acids upon increase in chain length increase corroborates previously reported studies in poultry [42,43]. No significant differences were observed in apparent digestibility of α-linolenic acid or total n-3 fatty acids in control and CAM10 diet-fed birds.…”
Section: Nutrient Digestibilitysupporting
confidence: 92%
“…No significant differences were observed in apparent digestibility of α-linolenic acid or total n-3 fatty acids in control and CAM10 diet-fed birds. Higher apparent fecal digestibility of different polyunsaturated fatty acids compared with unsaturated fatty acids in broiler chickens were reported earlier [42]. Zelenka et al [43] observed that the digestibility of α-linolenic acid was significantly higher than that of linoleic acid.…”
Section: Nutrient Digestibilitymentioning
confidence: 73%
“…Information about the levels of fatty acids in the whole body of broiler chickens at the time of slaughter with regard to sex and the currently used modern hybrids is largely missing. For example (Poureslami et al 2010a) reported that sex has only a marginal effect on n-3 and n-6 PUFA metabolism and no effect on metabolism of SaFA and MUFA (Poureslami et al 2010b). In marked contrast to these earlier data, the results of our trial document the existence of effects of sex on FA levels.…”
Section: Originalcontrasting
confidence: 99%